Image‐Derived Assessment of Left Ventricular Mass in Fetal Myocardial Hypertrophy by 4‐Dimensional Echocardiography: An In Vitro Study. (1st April 2016) - Liu, Xin; Zhu, Meihua; Streiff, Cole; Sahn, David J.; Ashraf, Muhammad
Abstract : Objectives: This study tested the accuracy of new 4‐dimensional fetal echocardiography to evaluate left ventricular (LV) mass in an experimental model of fetal myocardial hypertrophy. Methods: Ten fresh rabbit hearts were studied. Fetal myocardial hypertrophy was simulated by fixing different amounts of myocardial tissue to the LV epicardium. A small latex balloon was mounted on vinyl tubing and fixed within each LV cavity. The proximal end of the tube was attached to a pulsatile pump apparatus. The pump was calibrated to deliver stroke volumes of 2 and 4 mL at stroke rates of 60 and 120 beats per minute (bpm). Four‐dimensional data were acquired and analyzed with quantification software. Reference values for LV mass were determined by the displacement method. Results: Echo‐derived measurements of LV mass showed good correlations with reference values at all stroke rates and stroke volumes: at 2 mL and 60 bpm, r = 0.95; at 2 mL and 120 bpm, r = 0.95; at 4 mL and 60 bpm, r = 0.93; and at 4 mL and 120 bpm, r = 0.95 ( P < .01 for all values). There was also excellent interobserver ( r = 0.98; mean difference of −0.32 g; −4.4% of the mean) and intraobserver ( r = 0.98; mean difference of −0.28 g; −3.8% of the mean) agreement. Conclusions: In this controlled in vitro study, high‐resolution 4‐dimensional echocardiography was shown to accurately assess LV mass and have the potential to evaluate fetal myocardial hypertrophy.